114 Stability of Gut Microbiome Alpha Diversity During Combined Sleep Restriction and Circadian Misalignment. (3rd May 2021) - Withrow, Dana; Gonzalez, Antonio; Sprecher, Kate; Depner, Christopher; Burke, Tina; Fleshner, Monika; Lowry, Christopher; Turek, Fred; Vitaterna, Martha; Dorrestein, Pieter; Knight, Rob; Wright, Kenneth
Abstract: Introduction: Disturbed gut microbiome diversity has been associated with poor health outcomes and various disease states. We investigated the impact of combined sleep restriction (3h time in bed [TIB] sleep opportunities per day) and circadian misalignment (daytime sleep and nighttime wakefulness) on gut microbiome alpha diversity in healthy young individuals in a controlled laboratory setting. Methods: Twenty healthy adults (8 female), mean age (±SD) 25.65(±4.2) completed a 39-day protocol consisting of two laboratory visits lasting 4 days each. Two weeks of ambulatory monitoring prior to laboratory visits confirmed 8h habitual sleep duration per night. Participants consumed energy-balanced diets, identical within participants, 2 days before and during the laboratory visits. The laboratory visits consisted of sleep opportunities as follows: night 1 (8h TIB), night 2 (3h TIB), day 3 (3h TIB) and day 4 (3h TIB). Fecal microbiome samples were obtained at baseline between day 1 and 2, and during sleep and circadian disruption (between day 3 and 4). Alpha diversity measures were calculated using Pielou's evenness, Faith's phylogenetic diversity and number of observed OTUs. Results: Linear mixed models with subject as a random factor and visit as a fixed factor were performed to assess whether any alpha diversity measures changed during sleep and circadian disruption compared to baseline. Alpha diversity did not change significantly between baseline and sleep and circadian disruption (all p > 0.57). Additionally, intraclass correlation coefficients (ICCs) were calculated at baseline and during sleep and circadian disruption to determine if alpha diversity measures showed trait-like stability at both time points. ICCs were substantial to almost perfect (ICC 0.64–0.84) at baseline and substantial (ICC 0.70–0.80) during sleep and circadian disruption. Conclusion: Four days of combined sleep restriction and circadian misalignment does not appear to alter alpha diversity of gut microbiota species in healthy adults. Further, substantial to almost perfect intraclass correlation coefficients suggest alpha diversity of the human microbiome is stable during combined sleep and circadian perturbation and that examination at the level of microbiota community composition and functional outcomes are needed. Support (if any): Office of Naval Research MURI (N00014- 15-1-2809), NIH/NCATS (UL1TR002535), NIH T32 HL149646, CU Undergraduate Research Opportunities.